# Floor of x+m over n

## Theorem

Let $m, n \in \Z$ such that $n > 0$.

Let $x \in \R$.

Then:

$\left\lfloor{\dfrac {x + m} n}\right\rfloor = \left\lfloor{\dfrac {\left\lfloor{x}\right\rfloor + m} n}\right\rfloor$

where $\left\lfloor{x}\right\rfloor$ denotes the floor of $x$.

### Corollary

Let $n \in \Z$ such that $n > 0$.

Let $x \in \R$.

Then:

$\left \lfloor{\dfrac x n}\right \rfloor = \left \lfloor{\dfrac {\left \lfloor{x}\right \rfloor} n}\right \rfloor$

where $\left\lfloor{x}\right\rfloor$ denotes the floor of $x$.

## Proof 1

Let:

$y = x - \floor x$
$M = m + \floor x$

We now have:

$(1): \quad 0 \le y < 1$

and

$\floor y = 0$

Write:

$(2): \quad M = k n + r$

with $k \in \Z$ and $0 \le r \le n - 1$.

By $(1)$ and $(2)$:

$(3): \quad 0 \le r + y < n - 1 + 1 = n$

We have:

 $\displaystyle \floor {\dfrac {y + M} n}$ $=$ $\displaystyle \floor {\dfrac {y + r} n + k}$ $\displaystyle$ $=$ $\displaystyle k + \floor {\dfrac {r + y} n}$ $\displaystyle$ $=$ $\displaystyle k$ from $(3)$ $\displaystyle$ $=$ $\displaystyle \floor {\dfrac M n}$

Substituting $y$ and $M$, we obtain:

 $\displaystyle \floor {\dfrac {x - \floor x + m + \floor x} n }$ $=$ $\displaystyle \floor {\dfrac {x + m} n }$ $\displaystyle$ $=$ $\displaystyle \floor {\dfrac {m + \floor x} n}$

and the result follows.

$\blacksquare$

## Proof 2

Let $f: \R \to \R$ be the real function defined as:

$\forall x \in \R: f \left({x}\right) = \dfrac {x + m} n$

It is clear that $f$ is both strictly increasing and continuous on the whole of $\R$.

Let $\dfrac {x + m} n \in \Z$.

Then:

 $\displaystyle \exists s \in \Z: \dfrac {x + m} n$ $=$ $\displaystyle s$ $\displaystyle \leadsto \ \$ $\displaystyle x + m$ $=$ $\displaystyle n s$ $\displaystyle \leadsto \ \$ $\displaystyle x$ $=$ $\displaystyle n s - m$ $\displaystyle$ $\in$ $\displaystyle \Z$

Thus:

$\forall x \in \R: f \left({x}\right) \in \Z \implies x \in \Z$

So the conditions are fulfilled for McEliece's Theorem (Integer Functions) to be applied:

$\left \lfloor{f \left({x}\right)}\right \rfloor = \left \lfloor{f \left({\left \lfloor{x}\right \rfloor}\right)}\right \rfloor \iff \left(f \left({x}\right) \in \Z \implies x \in \Z)\right)$

Hence the result.

$\blacksquare$